Structural characterization of lignin from leaf sheaths of “dwarf cavendish” banana plant - Oliveira, Lúcia (2021)
Dioxane lignin (DL) isolated from leaf sheaths of banana plant (Musa acuminata Colla var. cavendish) and in situ lignin were submitted to a comprehensive structural characterization employing spectroscopic (UV, FTIR, solid state 13C CP-MAS NMR, liquid state 13C and 1H NMR) and chemical degradation techniques (permanganate and nitrobenzene oxidation). Results obtained showed that banana plant leaf sheath lignin is of HGS type with a molar proportion of p-hydroxyphenyl (H)/guaiacyl (G)/syringyl (S) units of 12:25:63. Most of the H units in DL are terminal phenolic coumarates linked to other lignin substructures by benzyl and Cgamma-ester bonds in contrast to ferulates that are mainly ether linked to bulk lignin. It is proposed that banana plant leaf sheath lignin is chemically bonded to suberin-like components of cell tissues by ester linkages via essentially hydroxycinnamic acid residues. beta-O-4 structures (0.31/C6), the most abundant in DL, comprise mainly S units, whereas a significant proportion of G units is bonded by beta-5, 5-5', and 4-O-5' linkages contributing to ca. 80% of condensed structures in DL.